MicroRNA-134 targets KRAS to suppress breast cancer cell proliferation, migration and invasion - Su, Xiaomei (Oncol Lett, 2017)
The expression patterns and functions of microRNA-134 (miR-134) have been previously studied in numerous types of cancer. To the best of our knowledge, this is the first study of miR-134 in human breast cancer. In the present study, the expression patterns, biological functions and underlying molecular mechanisms of miR-134 in human breast cancer were investigated. Reverse transcription-quantitative polymerase chain reaction evaluated the expression of miR-134 in human breast cancer tissues, matched normal adjacent tissues, breast cancer cell lines and a normal mammary epithelial cell line. Following transfection with miR-134, an MTT assay, cell migration assay, cell invasion assay, western blot analysis and a luciferase assay were performed on the MCF-7 and MDA-MB-231 human breast cancer cell lines. The findings revealed that miR-134 expression levels were significantly downregulated in breast cancer cells. Statistical analysis demonstrated that low expression of miR-134 was significantly associated with lymph node metastasis, TNM stage and reduced cell differentiation. It was observed that miR-134 inhibited the growth, migration and invasion of breast cancer cells. Additionally, the present study indicated that miR-134 may directly target the Kirsten rat sarcoma viral oncogene homolog in breast cancer tissues. These results suggest that miR-134 may be used as a potential therapeutic biomarker in breast cancers.